Enseñanza de la nomenclatura de química inorgánica como lenguaje científico especializado en el área de química (2020)
The thesis proposes a didactic strategy, focused on the teaching-learning of the nomenclature in inorganic chemistry, which is a specialized language very typical of this discipline. In which it is necessary to be able to understand the name of the different compounds on a global level, taking into account their rules according to the International Union of Pure and Applied Chemistry (IUPAC). It was carried out with the context of the San José of Castro Rural Educational Center, located in the Castro District of the municipality of Arboledas (North of Santander). The didactic strategy was applied in 35 students of the tenth grade, in the area of chemistry, being the teacher author of this thesis. It is about moving from a rote learning and mechanical pedagogical forms to other active and related to the daily and experiential environments of the students. The methodology used was descriptive with a qualitative approach; observing that, through the application of various nomenclature exercises with the students, there was progress in the appropriation of the language of inorganic chemistry, focusing primarily on identifying the presence of chemical compounds in their daily lives.